2020
DOI: 10.1186/s12870-020-02426-z
|View full text |Cite
|
Sign up to set email alerts
|

Integrated small RNA and mRNA expression profiles reveal miRNAs and their target genes in response to Aspergillus flavus growth in peanut seeds

Abstract: Background: MicroRNAs are important gene expression regulators in plants immune system. Aspergillus flavus is the most common causal agents of aflatoxin contamination in peanuts, but information on the function of miRNA in peanut-A. flavus interaction is lacking. In this study, the resistant cultivar (GT-C20) and susceptible cultivar (Tifrunner) were used to investigate regulatory roles of miRNAs in response to A. flavus growth. Results: A total of 30 miRNAs, 447 genes and 21 potential miRNA/mRNA pairs were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 86 publications
(105 reference statements)
2
23
0
1
Order By: Relevance
“…The size distributions of the four sRNA libraries showed similar patterns ( Figure 2 ). The 24-nt reads were the most abundant class (about 50%), followed by 21-nt reads (17%) ( Figure 2 ), in agreement with previous reports on cotton and other plant species ( An et al, 2015 ; Li et al, 2019 ; Zhao et al, 2020 ). On the average, 84.18% of the reads were successfully aligned to the AD genome of G .…”
Section: Resultssupporting
confidence: 92%
“…The size distributions of the four sRNA libraries showed similar patterns ( Figure 2 ). The 24-nt reads were the most abundant class (about 50%), followed by 21-nt reads (17%) ( Figure 2 ), in agreement with previous reports on cotton and other plant species ( An et al, 2015 ; Li et al, 2019 ; Zhao et al, 2020 ). On the average, 84.18% of the reads were successfully aligned to the AD genome of G .…”
Section: Resultssupporting
confidence: 92%
“…We also drew similar conclusions by comparing the distribution of sRNA richness in other plants such as peanuts, rapeseed, tomatoes, and radishes. However, we found that 18 nt sRNAs have the highest richness in wheat [ 31 , 33 , 48 , 49 , 50 ]. Such results indicated that the abundance of sRNAs may only slightly vary between species, regardless of experimental treatment and variety selection.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al [36] identi ed an important role of chitinase in peanut resistance to Aspergillus avus by differential analysis of transcriptomic and proteomic. Zhao et al [37] found that miRNAs could regulate peanut resistance to Aspergillus avus. Zhang et al [38] suggested that nonmetabolizable glucose analogs could inhibit the synthesis of a atoxin and promote Aspergillus avus to produce kojic acid.…”
Section: Discussionmentioning
confidence: 99%